Nurse's activity in the intensive therapy unit identification of sepse's signs and symptoms (Research, Society and Development, 2020)
Sepsis is considered to be one of the most fatal diseases worldwide. It is a disease of high morbidity and mortality, which treatment involves high costs and demands a service of excellence in the emergency and intensive care units. Objective: describe the nursing care in the detection of signs and symptoms of sepsis. Methodology: The study was designed through a bibliographical review using studies of the last ten years. A search was performed in the Virtual Health Library (VHL) in 2019, as well as in the databases: Bireme, Lilacs and Scielo, with the following descriptors: "sepsis", "nursing care", "intensive care". Results: The national scenario pointed out that patients with sepsis or septic shock, causing 55% of these patients to die, occupy approximately 30% of ICU beds in Brazil. Conclusion: The nursing professional works by offering all the necessary support, using their scientific knowledge so that the care is individualized and directed to the real needs of the individual.